Effects of Mass Media Coverage on Timing and Annual Receipt of Influenza Vaccination among Medicare Elderly - Yoo, Byung-Kwang (Blackwell Science Inc, 2010)
OBJECTIVE: To measure the association between mass media coverage on flu-related topics and influenza vaccination, regarding timing and annual vaccination rates, among the nationally representative community-dwelling elderly. DATA SOURCE: Years 1999, 2000, and 2001 Medicare Current Beneficiary Survey. STUDY DESIGN: Cross-sectional survival analyses during each of three influenza vaccination seasons between September 1999 and December 2001. The outcome variable was daily vaccine receipt. We measured daily media coverage by counting the number of television program transcripts and newspaper/wire service articles, including keywords of influenza/flu and vaccine/shot shortage/delay. All models' covariates included three types of media, vaccine supply, and regional/individual factors. PRINCIPAL FINDINGS: Influenza-related reports in all three media sources had a positive association with earlier vaccination timing and annual vaccination rate. Four television networks' reports had most consistent positive effects in all models, for example, shifting the mean vaccination timing earlier by 1.8–4.1 days (p<.001) or increasing the annual vaccination rate by 2.3–7.9 percentage points (p<.001). These effects tended to be greater when reported in a headline rather than in text only and if including additional keywords, for example, vaccine shortage/delay. CONCLUSIONS: Timing and annual receipt of influenza vaccination appear to be influenced by media coverage, particularly by headlines and specific reports on shortage/delay.